2020
DOI: 10.1158/1055-9965.epi-19-1628
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Acrylamide and Risk of Breast, Endometrial, and Ovarian Cancers: A Systematic Review and Dose–Response Meta-analysis

Abstract: Acrylamide is a probable human carcinogen. Aside from occupational exposures and smoking, diet is the main source of exposure in humans. We performed a systematic review of the association between estimated dietary intake of acrylamide and risk of female breast, endometrial, and ovarian cancers in non-experimental studies published through February 25, 2020, and conducted a doseresponse meta-analysis. We identified 18 papers covering 10 different study populations: 16 cohort and 2 case-control studies. Acrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 72 publications
1
46
0
1
Order By: Relevance
“…Several studies have focused on investigating the toxicology of AA, and assessing the health risks of dietary exposure to AA in different food products [ 9 , 10 , 11 , 12 ]. The Food and Agriculture Organization/World Health Organization (FAO/WHO) reported that dietary AA exposure can vary between 0.3 and 0.8 μg/kg BW/day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on investigating the toxicology of AA, and assessing the health risks of dietary exposure to AA in different food products [ 9 , 10 , 11 , 12 ]. The Food and Agriculture Organization/World Health Organization (FAO/WHO) reported that dietary AA exposure can vary between 0.3 and 0.8 μg/kg BW/day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Netherlands cohort study on diet and cancer, increased risks of postmenopausal endometrial and ovarian cancer were reported with an increase in dietary AA intake [ 11 ]. Another report suggested that prediagnostic exposure to acrylamide, measured by AA-hemoglobin and glycidamide-hemoglobin adducts, could be related to mortality among breast cancer patient, especially those with endocrine-related types of breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reviews and meta-analyses performed in humans did not report any association between dietary AA intake and the risk of cancer for most organs susceptible to AA-induced carcinogenesis in rodents. This was shown to be the case for lung [ 49 ], breast cancer [ 50 , 51 , 52 , 53 , 54 ], and most studies of ovary cancer [ 52 , 55 , 56 ]. Only one recent study [ 54 ] reported a slight increased risk of ovarian cancer upon AA exposure.…”
Section: Impact Of Aa On Cancer Risk In Humansmentioning
confidence: 99%
“…In humans, the data on AA and endometrial cancer risk are somewhat inconsistent. While some studies and meta-analyses reported no association between dietary AA intake and endometrial cancer [ 52 , 57 , 58 ], others reported increased risk [ 51 , 54 , 56 ]. No associations were reported between AA intake and the risk of skin cancer, particularly in females, which represented the most sensitive gender for this type of cancer in rodents [ 59 ].…”
Section: Impact Of Aa On Cancer Risk In Humansmentioning
confidence: 99%
“…HBM4EU, which is the most recent of the described projects, has, so far, resulted in one publication that addressed breast cancer in a sample of 585 females (age 28–85 years), who were enrolled between 2007 and 2011 [ 94 ]. A further review and the projects overall ambition promise that further work will follow [ 1 ]. Ongoing and planned work strives to link human exposure to general health status by expanding chemical analyses to biospecimen available from established health cohort studies [ 96 ] and address pesticide mixture exposure and associated health effects [ 101 ].…”
Section: Main Textmentioning
confidence: 99%